Effect of Abhyantara Snehapana and Vamana Karma in Patients with Normal and Abnormal to Lipid Profile (AYUSHDHARA, 2024)
In the recent years, India and other developing countries are witnessing a rapid escalation in lifestyle disorders like diabetes, coronary artery disease, obesity, hypothyroidism, etc. The prime causative factor for all the lifestyle disorders is hyperlipidemia or dyslipidemia. Dyslipidemia is defined as a metabolic disorder that occurs due to abnormal blood lipid levels. This may lead to increase in the chances of atherosclerosis, heart attacks, stroke and other circulatory disorders. The abnormal lipid levels may include increase in triglycerides, VLDL, LDL and decrease in HDL. Vamana karma, a bio-purificatory emesis, being the major Panchakarma therapy has its greatest influence on almost all the lifestyle disorders. Lifestyle disorders aren’t possible without the involvement of Kapha dosha and Medho dhatu. Vamana is the first line of choice in the treatment of disorders caused by the aggravation of Kapha Dosha or Kapha associated with Pitta dosha. Vamana karma involves a pre-procedure called Snehapana, which include administration of high quantity of medicated lipids for a maximum period of seven days, followed by the bio-purificatory emesis or Vamana karma, a process of elimination of morbid Doshas from the oral route. Considering the high amounts of lipid usage in Snehapana, it becomes essential, to monitor its impact on lipid profile in patients undergoing Vamana karma for various etiologies. The present clinical study is of paramount importance as there were no previous studies on the impact of Sneha pana and Vamana in patients with both normal and abnormal lipid profiles. The statistical significance of results were quantitated by paired t test. Although Snehapana followed by Vamana, did not significantly alter levels of total cholesterol, and LDL, it did cause a significant reduction in triglycerides (p=0.0013) and VLDL (p=0.0038), improvement of HDL (P=0.02) in all the patients with abnormal lipid profile. However the values remained within the limit in patients with normal lipid parameters.